Boosting influenza vaccination rates through policy gamification - Lopes, Henrique (2024)
Lopes, H., Hermenegildo, C., & Franco, D. (2024). Boosting influenza vaccination rates through policy gamification: the ‘Let’s Control Flu’ project [abstract]. European Journal of Public Health, 34(Supplement 3), 837. https://doi.org/10.1093/eurpub/ckae144.2160